Serum CEACAM1 Correlates with Disease Progression and Survival in Malignant Melanoma Patients - Sapoznik Sivan; Faranesh Suzan; Ortenberg Rona; Hamburger Tamar; Barak Vivian; Peretz Tamar; Schachter Jacob; Markel Gal; Lotem Michal (Clinical and Developmental Immunology)
The search for melanoma biomarkers is crucial, as the incidence of melanoma continues to rise. We have previously demonstrated that serum CEACAM1 (sCEACAM1) is secreted from melanoma cells and correlates with disease progression in metastatic melanoma patients. Here, we have used a different cohort of melanoma patients with regional or metastatic disease (N=49), treated with autologous vaccination. By monitoring sCEACAM1 in serum samples obtained prior to and after vaccination, we show that sCEACAM1 correlates with disease state, overall survival, and S100B. The trend of change in sCEACAM1 following vaccination (increase/decrease) inversely correlates with overall survival. DTH skin test is used to evaluate patients’ anti-melanoma immune response and to predict response to vaccination. Importantly, sCEACAM1 had a stronger prognostic value than that of DTH, and when sCEACAM1 decreased following treatment, this was the dominant predictor of increased survival. Collectively, our results point out the relevance of sCEACAM1 in monitoring melanoma patients.